DEVELOPING A MULTIREPRESENTATION LEARNING MODEL BASED ON LOCAL WISDOM TO TRANSFORM CHARACTER FOR STUDENTS OF 5-6 YEARS OLD - Novianti Retno Utami; Khikmah Novitasari (Early Childhood Education and Development Journal, 2019)
This research aimed to: (1) develop a multirepresentation learning model, (2) reveal the effectiveness of the developed multirepresentation learning model, and (3) transform character for students of 5-6 years old. The data were collected using a validation sheet, questionnaire of teacher’s responses, and observation. The data were analyzed using the independent sample t test with a significance level of 0,05. The result of the assessment by the material expert validator was “Good”. The research finding revealed that the multirepresentation learning model in terms of the content expediency, the language, the presentation, and the graphic component were categorized “Very Good”. There was a difference in the nation spirit character between the experimental class and the control class after the teacher used the multirepresentation learning model with p < 0.05, and there was also a significant increase, with p = 0.000.